Red Rock's secret a western trio - Brand, Max (Waterville, Me. Five Star, 2006)
In Cuttle's Hired Man Bill Warner and Chick Newton are two cowboys who formed a friendship. Seven years later, Chick Newton encounters Bill Warner again in a small desert town in Arizona Territory. Time has aged them both, but Chick is sure that it is the same man, only Bill Warner denies it. His name, he insists, is Joe Tucker. The Girl They Left Behind Them is an extraordinary story about big Jack Innis, who finds himself attracted to Stella Cornish, daughter of the local sheriff. The problem for Jack is that Miles Ogden claims Stella as his girlfriend and has terrified or intimidated every other man who has ever dared show any interest in her. Speedy is a loner, able to outwit and outmanoeuvre even the deadliest men without the use of a gun. Speedy lives in obscurity because of his enemies, but in Red Rock's Secret, Jessica Fenton Wilson is on his trail.
Cuttle's hired man -- The girl they left behind -- Red Rock's secret.
87858
Keywords: Western stories; Manners and customs